2018
DOI: 10.7567/jjap.57.030311
|View full text |Cite
|
Sign up to set email alerts
|

Turbostratic stacked CVD graphene for high-performance devices

Abstract: We have fabricated turbostratic stacked graphene with high-transport properties by the repeated transfer of CVD monolayer graphene. The turbostratic stacked CVD graphene exhibited higher carrier mobility and conductivity than CVD monolayer graphene. The electron mobility for the three-layer turbostratic stacked CVD graphene surpassed 10,000 cm 2 V %1 s %1 at room temperature, which is five times greater than that for CVD monolayer graphene. The results indicate that the high performance is derived from mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
(39 reference statements)
4
34
0
Order By: Relevance
“…Moreover, the field‐effect mobility observed from the turbostratic multilayer graphene is higher than that observed from the AB‐stacked multilayer graphene as shown in Figure a. Actually, it has been reported that a trilayer turbostratic‐stacked graphene prepared by the repeated transfer of Cu‐CVD monolayer graphene exhibits higher carrier mobility than the monolayer graphene . Therefore, it is considered that the electronic band structure in the grown multilayer graphene in our study preserves the linear dispersion as a quasimonolayer due to a weak interlayer coupling associated with the formation of turbostratic stacking observed in the STEM images (Figure e–g).…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, the field‐effect mobility observed from the turbostratic multilayer graphene is higher than that observed from the AB‐stacked multilayer graphene as shown in Figure a. Actually, it has been reported that a trilayer turbostratic‐stacked graphene prepared by the repeated transfer of Cu‐CVD monolayer graphene exhibits higher carrier mobility than the monolayer graphene . Therefore, it is considered that the electronic band structure in the grown multilayer graphene in our study preserves the linear dispersion as a quasimonolayer due to a weak interlayer coupling associated with the formation of turbostratic stacking observed in the STEM images (Figure e–g).…”
Section: Resultsmentioning
confidence: 59%
“…Figure a–c shows the transfer characteristics before and after introducing ethanol gas for pristine graphene FET (P‐GFET), sequence‐1‐modified graphene FET (SQ1‐GFET), and sequence‐2‐modified graphene FET (SQ2‐GFET), respectively. Ambipolar characteristics were observed for graphene FETs, owing to a zero bandgap of graphene . The field‐effect mobilities for the devices were estimated to be ≈2000 cm 2 (V·s) −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, graphene growth technology has greatly matured in recent years [ 154 , 155 , 156 ]. Moreover, turbostratic graphene has been proposed as a means of suppressing deleterious electrical disturbances in oxide layers under graphene [ 157 , 158 ]. However, there are still a number of important challenges that must be addressed in order to integrate silicon-based semiconductor technology with graphene in terms of uniformity and size [ 159 ].…”
Section: Future Outlookmentioning
confidence: 99%